(3ETQGb GdEUHGM aj efGbH GdNeSI GdCTHGMs - (3HQgGf GdOjf EHQGgje Hf eMeO Hf Ydj Hf fRGQ GdUfYGfjs
(3ChdgG (B:s
(3MeOkG GdehLO GdcdjGJ JMbjbkG hJbOjQkG s
(3BNQgG (B:s
(3hjUdi Ydi SjO GdCfGe UdGI JJQi Ydi eeQ GdSGYGJ hMSHfG Gddg hfYe Gdhcjd , hfYe Gdehdi hfYe GdfUjQ s
(3JHUQGJ GdCUd (B:s
(3bQFJ Ydi GdeDda (B: (3hbQCgG GdbGSe Hf eMeO Hf bGSe Hf CHj WhjdI GdUYOi GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdSjO eMeO Hf eMeO Hf ESeGYjd GdeXgQ s
Keywords: (3GdJGQjNs